PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP INDEKS PEMBANGUNAN MANUSIA DENGAN ALOKASI BELANJA MODAL SEBAGAI VARIABEL INTERVENING (STUDI PADA KABUPATEN/KOTA PROVINSI RIAU PERIODE 2011-2015) - Hasan, Mudrika Alamsyah; Suryo Agung, Muhammad Fajar (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study aimed to examine the affect of local revenue, general allocation fund andspecial allocation fund fund to human development index with capital expenditure asintervening variable. The population of study is budget realization report of revenueand expenditure regional in Riau province from 2011-2015 and table of humandevelopment index from 2011-2015. The method of this study used purposivesampling and obtain each 50 data as a sample. The sampleâs criterias of this studyare publishing budget realization report annually from 2011-2015 and having humandevelopment index data from 2011-2015. Methods of Analysis is conducted withpath analysis using SPSS (Statistical Product and Service Solutions)Version 21.Test results that have been done. The partial regression test I (t test I) shows thatLocal Revenue affects the Capital Expenditure Allocation with P <0.05 (P = 000).General Allocation Fund affect the Capital Expenditure Allocation with P> 0,05 (P =,021). The Special Allocation Fund has no effect on Capital Expenditure Allocationwith P> 0.05 (P = ,380). Partial regression test II (t test II) indicates that LocalRevenue affects the Human Development Index with P <0.05 (P = 000). GeneralAllocation Fund has no effects on Human Development Index with P <0.05 (P =.057). The Special Allocation Fund has no effect on Human Development Index withP> 0.05 (P = .078). Capital Expenditure did not affect the Human DevelopmentIndex with P> 0.05 (P = .101). The results of this study also indicate that LocalRevenue does not indirectly affect the Human Development Index through theCapital Expenditure Allocation by beta coefficient standard (, 916) + (-, 091504) = (,0824496). The General Allocation Fund does not indirectly affect the HumanDevelopment Index through the Capital Expenditure Allocation with the standardbeta coefficients (,158) + (,044992) = (,202992). The Special Allocation Fundindirectly affects the Human Development Index through the Capital ExpenditureAllocation with the standard beta coefficients (-,137) + (-,016568) = (-,153568). Thecoefficient of determination in this research is 75.7%. Four of these variables affectthe dependent variable is 75.3%, while 24.7% is influenced by other variables thatare not discussed in this study.